Deep-Sea Nematodes of the Mozambique Channel: Evidence of Random Community Assembly Dynamics in Seep Sediments - Macheriotou, Lara; Rigaux, Annelien; Olu, Karine; Zeppilli, Daniela; Derycke, Sofie; Vanreusel, Ann (Frontiers in Marine Science, 2021)
Cold seeps occur globally in areas where gases escape from the seafloor, occasionally resulting in the formation of topographic depressions (pockmarks), characterised by unique physicochemical conditions such as anoxic and sulphuric sediments. Free-living marine nematodes tend to dominate the meiofaunal component in such environments, often occurring at extremely high densities and low richness; the mechanisms defining community assembly in areas of fluid seepage, however, have received little attention. Here we focus on a low-activity pockmark at 789 m in the Mozambique Channel (MC). We assessed the diversity, co-occurrence patterns and phylogenetic community structure of nematodes at this bathyal site to that of a nearby reference area as well as abyssal sediments using metabarcoding. In addition, we compared our molecularly-derived diversity estimates to replicate samples identified morphologically. Overall, nematode Amplicon Sequence Variants (ASVs) and generic richness were similar between Pockmark and Abyssal sediments, but lower compared to the Reference area. Although more than half the genera were shared, over 80% of ASVs were unique within each area and even within each replicate core. Even though both methodologies differentiated the Pockmark from the Reference and Abyssal sites, there was little overlap between the molecularly and morphologically identified taxa, highlighting the deficit of reference sequences for deep-sea nematodes in public databases. Phylogenetic community structure at higher taxonomic levels was clustered and did not differ between the three areas yet analysis within three shared and dominant genera (Acantholaimus, Desmoscolex, Halalaimus), revealed randomness with respect to phylogeny as well as co-occurrence which was exclusive to the Pockmark area. These patterns point to the influence of neutral dynamics at this locality resulting from the stochastic sampling of early colonising taxa, the successional stage at sampling and/or the functional redundancy within the investigated genera.